MODERNISASI TASAWUF DALAM PENGEMBANGAN PENDIDIKAN KARAKTER - Restu Andrian (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2019)
Sufism is a science that examines the process of beautifying morals in the form of birth and purification of the soul spiritually to achieve happiness in the world and the hereafter. In the context of broader modernism, Sufism is also associated with psychology and other general sciences. This phenomenon illustrates that Sufism can be interpreted comprehensively with various approaches which will then produce various kinds of innovations in the development of knowledge, including education. Sufism can be applied and applied through a character education approach that emphasizes value planting. The dynamics of modern life grow along with human needs that continue to grow. The need that continues to grow will then backfire for humans and their groups if they are not able to be packaged in a useful context. The problems of modern life can be packaged in Sufism scholarship that has been modernized in character education.